Exposure of Mycobacterium tuberculosis to human alveolar lining fluid shows temporal and strain-specific adaptation to the lung environment - Allué-Guardia, Anna; Garcia-Vilanova, Andreu; Schami, Alyssa M.; Olmo-Fontánez, Angélica M.; Hicks, Amberlee; Peters, Jay; Maselli, Diego J.; Wewers, Mark D.; Wang, Yufeng; Torrelles, Jordi B. (Frontiers in Tuberculosis, 2024)
Upon infection, Mycobacterium tuberculosis (M.tb) reaches the alveolar space and comes in close contact with the lung mucosa or human alveolar lining fluid (ALF) for an uncertain period of time prior to its encounter with alveolar cells. We showed that homeostatic ALF hydrolytic enzymes modify the M.tb cell envelope, driving M.tb-host cell interactions. Still, the contribution of ALF during M.tb infection is poorly understood. Here, we exposed 4 M.tb strains with different levels of virulence, transmissibility, and drug resistance (DR) to physiological concentrations of human ALF for 15-min and 12-h, and performed RNA sequencing. Gene expression analysis showed a temporal and strain-specific adaptation to human ALF. Differential expression (DE) of ALF-exposed vs. unexposed M.tb revealed a total of 397 DE genes associated with lipid metabolism, cell envelope and processes, intermediary metabolism and respiration, and regulatory proteins, among others. Most DE genes were detected at 12-h post-ALF exposure, with DR-M.tb strain W-7642 having the highest number of DE genes. Interestingly, genes from the KstR2 regulon, which controls the degradation of cholesterol C and D rings, were significantly upregulated in all strains post-ALF exposure. These results indicate that M.tb-ALF contact drives initial bacterial metabolic and physiologic changes, which may have implications in the early events of M.tb infection.